2013
DOI: 10.7860/jcdr/2013/5545.3278
|View full text |Cite
|
Sign up to set email alerts
|

A Subjective Assessment of Perceived Clarity of Indirect Digital Images and Processed Digital Images with Conventional Intra-oral Periapical Radiographs

Abstract: Indirectly digitizing the radiographs by employing a digital camera and further digitally processing the images resulted in an improvement in their perceived clarity and they enhanced their diagnostic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This study used film X-rays, and currently digital X-rays are commonly performed. There may be differences in the interpretation of the two types of images,32, 33, 34, 35 and this was not evaluated in the current study. An ideal method of performing the study would have been to perform digital radiographs prior to extraction of the teeth.…”
Section: Discussionmentioning
confidence: 96%
“…This study used film X-rays, and currently digital X-rays are commonly performed. There may be differences in the interpretation of the two types of images,32, 33, 34, 35 and this was not evaluated in the current study. An ideal method of performing the study would have been to perform digital radiographs prior to extraction of the teeth.…”
Section: Discussionmentioning
confidence: 96%
“…They concluded that the quality of scanned digital images was superior to that of original conventional films. Similarly, Malleshi et al [ 15 ] analyzed the clarity and diagnostic value of digital images in comparison with conventional intraoral radiographs. They demonstrated that digitized images resulted in enhanced image clarity and improved diagnostic quality; however, their findings were not substantiated by the present study.…”
Section: Discussionmentioning
confidence: 99%